Lack of Association Between Interleukin 28B Polymorphism and Vertical Transmission of Hepatitis C. Issue 6 (December 2017) - Psaros Einberg, Afrodite; Duberg, Ann-Sofi; Filipovich, Olga; Nyström, Jessica; Zhirkov, Anton; Brenndörfer, Erwin D.; Frelin, Lars; Rukoiatkina, Elena; Lobzin, Yuriy; Sällberg, Matti; Fischler, Björn; Lutckii, Anton
ABSTRACT: Objectives: Single genetic nucleotide polymorphism ( rs12979860 ) near the gene for interleukin 28B (IL28B) is known to be of importance for frequency of spontaneous clearance and treatment outcome in interferon-based therapies in patients with hepatitis C virus (HCV) infection. The aim of the present study was to investigate whether IL28B polymorphism in children and/or their mothers plays a role in vertical transmission of HCV (HCV-VT). Methods: Plasma samples from 59 infected women, 76 uninfected children born to infected mothers, and 47 children with known vertically transmitted HCV infection, were analysed for IL28B polymorphism and classified by the IL28B genotype (C/C, C/T, and T/T) and by viral genotype. Results: The proportion of children with genotype C/C was the same in the vertically infected (36%, 17/47) and the exposed uninfected children (38%, 29/76). No difference was seen when stratifying for viral genotype. There was no association between mothers' IL28B genotype and the risk of vertical transmission. Conclusions: Regardless of viral genotype we found no association between IL28B genotype and the risk of HCV-VT. The IL28B genotype CC, which has been shown to be favourable in other settings, was not protective of HCV-VT. Thus, other factors possibly associated with the risk of HCV-VT need to be explored.